How metropolis impact the Tourism-Residence Relationship of its suburb: A case study of Naka-Uji area, Uji City, Kyoto Prefecture - Cui, Shuailing; Nakajima, Naoto (International Planning History Society Proceedings, 2024)
Metropolis can influence populations, industries, physical space, living environment, and more of its suburbs. Suburbs serve as a buffer space between urban and towns, carrying a series of problems in urban development. Kyoto is one of the metropolises in Japan which is famous for its long history. Uji, located on the outskirts of Kyoto, has also prospered in tourism because of its long history and the World Heritage Byodoin Temple. Through historical data, ancient map surveys, and statistics, this research concludes that metropolis plays a decisive role in the tourism development of their surrounding suburbs and that their policies about the tourism development will affect the tourism activities in its suburban and then impact on the number, layout, use of buildings and living environment in the suburbs.